Russian understanding of strategic communication - Drandrova, Anastasia (2019)
Strategic communication is relatively new concept that originates in Unites States. Despite, functions of the concept are highly applied in various fields. Strategic communication is well studied in Western world, while Russian understanding of the concept are poor. For this reason, this study is aimed to provide Russian academic understanding of strategic communication.